Numerical simulations of the SF6-N2 mixed gas streamer discharge development process - Lijun Wang (AIP Advances, 2019)
In recent years, as environmental protection requirements have expanded, SF6/N2 mixed gases have been selected as an insulating medium for high-voltage equipment such as GIL (gas insulated transmission line) without undertaking breaking tasks, which is superior in terms of insulation, economy and environmental protection. The development of streamers and the two-dimensional distribution of positive and negative ions over time in an SF6/N2 mixed gas system are shown in this research. The SF6/N2 mixed gas is adopted as the research object, and the discharge model for a needle-plate electrode under mixed gas conditions is built. COMSOL Multiphysics is used to develop a fluid dynamics model for the SF6/N2 mixed gas discharge in a non-uniform field. The spatio-temporal evolution processes for the electron, positive ion and negative ion densities and the electric field strength during discharge are obtained through numerical simulations. At the same time, the influence of the voltage amplitude and mixed gas ratio on the development process of streamers is studied. The presented simulation results can provide a certain microscopic interpretation for the needle-plate discharge defects that appear in power equipment using SF6/N2 mixed gas.